2018
DOI: 10.1029/2018jg004447
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation of Oxygen to Oxygen Minimum Zone Due to Anticyclonic Eddies in the Bay of Bengal

Abstract: Intense oxygen minimum zone (OMZ) occurs in the middepth of the Eastern Tropical Pacific (ETP), Arabian Sea (AS), and Bay of Bengal (BoB). However, the occurrence of anammox/denitrification was reported only in the ETP and AS and its absence in the BoB is attributed to presence of traces of dissolved oxygen (DO). Anticyclonic eddies (ACEs) supply high-nutrient, organic-rich, and oxygen-poor waters from the coastal upwelling regions leading to strengthening of OMZ in the offshore of AS and ETP. In the absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 52 publications
(80 reference statements)
3
30
0
Order By: Relevance
“…However, external processes regularly inject substantial (~5 to 10 μmol/kg) amounts of oxygen into this OMZ. This observation is consistent with the findings of Sarma and Bhaskar (). The high oxygen in these events inhibits denitrification.…”
Section: Introductionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, external processes regularly inject substantial (~5 to 10 μmol/kg) amounts of oxygen into this OMZ. This observation is consistent with the findings of Sarma and Bhaskar (). The high oxygen in these events inhibits denitrification.…”
Section: Introductionsupporting
confidence: 94%
“…They found higher mean oxygen levels than seen by Bristow et al (), which were generated by periodic anticyclonic eddies passing through the BoB. However, the profiling float examined by Sarma and Bhaskar () was located further south than the region sampled by Bristow et al ().…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Higher DOP concentrations in the upper 100 m of water column were observed within ACE N and ACE S , and it was lower in the CE and NE regions (Figure 2h). It has been reported that convergence of oxygen-rich waters in ACE regions led to weakening of OMZ in the BoB (Sarma and Udaya Bhaskar, 2018;. It has been reported that convergence of oxygen-rich waters in ACE regions led to weakening of OMZ in the BoB (Sarma and Udaya Bhaskar, 2018;.…”
Section: Spatial Variations In Don and Dop Concentrations In The Westmentioning
confidence: 99%
“…High concentrations of dissolved organic carbon (DOC, Fernandes et al, 2008;Shah, et al, 2018) and dissolved organic nitrogen (DON, Letscher, et al, 2013) are found in the BoB and attributed to supply through river discharge. Recently, it was observed that anticyclonic eddies (ACEs) transport oxygen-rich waters to oxygen minimum zone (OMZ) due to convergence leading to weakening of OMZ (Sarma and Udaya Bhaskar, 2018;. Recently, it was observed that anticyclonic eddies (ACEs) transport oxygen-rich waters to oxygen minimum zone (OMZ) due to convergence leading to weakening of OMZ (Sarma and Udaya Bhaskar, 2018;.…”
Section: Introductionmentioning
confidence: 99%